2003
DOI: 10.1021/bi026745u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a Cis-Opened (10R)-N6-Deoxyadenosine Adduct of (9S,10R)-9,10-Epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene in a DNA Duplex,

Abstract: The solution structure of an 11-mer DNA duplex, d(CGGTCA*CGAGG) x d(CCTCGTGACCG), containing a 10R adduct at dA* that corresponds to the cis addition of the N(6)-amino group of dA(6) to (+)-(9S,10R)-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene was studied by 2D NMR methods. The NOESY cross-peak patterns indicate that the hydrocarbon is intercalated on the 5'-side of the modified base. This observation is the same as that observed for other oligonucleotides containing (10R)-dA adducts but opposite to that obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…1 A), which perfectly match a predicted favorable conformation of the adduct (21) and are practically identical to those found in NMR structures determined in the absence of a polymerase (Fig. 3A) (6,22). Because of the intercalation of the PAH, the dA*⅐dT base pair is distorted by 36°of buckle, 31°of propeller twist, and 10°o f base opening (23), and only one hydrogen bond is retained between this base pair (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1 A), which perfectly match a predicted favorable conformation of the adduct (21) and are practically identical to those found in NMR structures determined in the absence of a polymerase (Fig. 3A) (6,22). Because of the intercalation of the PAH, the dA*⅐dT base pair is distorted by 36°of buckle, 31°of propeller twist, and 10°o f base opening (23), and only one hydrogen bond is retained between this base pair (Fig.…”
Section: Resultssupporting
confidence: 81%
“…3A) and higher temperature factors. Structural characterization of BPDE-dA adducts by NMR to date has found the hydrocarbon intercalated only between base pairs and not in the major groove (5,6,24). To accommodate the PAH in the major groove without clashing with the neighboring base pairs, the dA* slides toward the major groove by nearly 2 Å (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent crystal structure has revealed the accommodation of a BPDE-adenine adduct, linked to N 6 of dA, within Dpo4. Two structures were resolved, including a proposed blocking structure with the BP moiety intercalated between adjacent base pairs, similar to that seen by high resolution NMR in duplex DNA (106), and a proposed bypass structure, with the BP moiety solvent-exposed in the major groove (76). The major groove structure showed that the enzyme can coerce the adduct into adopting a conformation that is disfavored in duplex DNA (106, 107) and on the nucleoside level (108).…”
Section: The Bulky (ϩ)-Trans-anti-[bp]-n 2 -Dg Adduct Causes Less Dismentioning
confidence: 86%
“…The stereoisomeric BaP DE adducts at dG and dA provide a variety of structural motifs within duplex DNA that have been well characterized by NMR studies (24,25). For cis-opened BaP DE-dG adducts, both 10R and 10S enantiomers cause flipping out of both the modified base and its complement from the DNA helix (26,27).…”
mentioning
confidence: 99%